Parkinson’s disease and exosomes: from pathogenesis to diagnosis and treatment - A. Mišeikaitė; P. Vaitkienė (Neurologijos seminarai)
Parkinson’s disease (PD) is considered the second most common neurodegenerative disease after Alzheimer’s disease, with a mean onset age of 55 years. Although the clinical symptoms, neuronal changes, and various molecular mechanisms involved in this neuropathological disorder have been studied for many years, the diagnosis and treatment of the disease remain challenging. Of great interest are exosomes, extracellular vesicles isolated from the cellular endosomal system. It has been investigated that most cells, including nerve cells, in the brain can secrete these 50-150 nm diameter vesicles which can affect protein activity and gene expression. Due to their internal content and ability to move in an intercellular environment, exosomes are considered to play an important role in the accumulation and transportation of various molecular markers, such as α-synuclein protein or microRNA (miRNA), and to take a part in inflammatory processes in nervous tissue. Since the content of the exosomes depends on the cell that secretes them and can change during the progression of the disease, exosome studies can help to understand the pathogenesis and control the course of the disease. There is growing evidence of the importance of exosomes for cell-to-cell communication, mediating the exchange of biological information and substances, and the ability to cross the blood-brain barrier. Due to their ability to cross the blood-brain barrier, exosomes may be promising for drug or molecular transportation and help in the development of more effective treatments for PD and other diseases of the nervous system. The article reviews the biogenesis of exosomes and their potential roles in the diagnosis, treatment, and long-term outcome of Parkinson’s disease.